Proceedings of the 9th International Conference on Computer Supported Education 2017
DOI: 10.5220/0006311103000307
|View full text |Cite
|
Sign up to set email alerts
|

Improving Communication in Online Learning Systems

Abstract: In this paper, we study communication in online learning systems using both quantitative and qualitative research methods. Quantitative methods provide the interaction statistics, while qualitative content analysis was used for categorisation of the messages. It turns out that 20% of the active participants dominate the online learning interactions, and more than 80% are passive consumers. From the categorization, we learned that most of the communication is not related to learning, but to technical problems (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
5
0
2
Order By: Relevance
“…The MGA analysis indicated that learner control and online communication have relatively higher factor loadings than others. We believe that these two factors are influenced by the learning platform based on Mayende et al (2017) and Taipjutorus (2012) . Thus, the learning platform can be considered as the mediating factor, which may be considered for further study in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The MGA analysis indicated that learner control and online communication have relatively higher factor loadings than others. We believe that these two factors are influenced by the learning platform based on Mayende et al (2017) and Taipjutorus (2012) . Thus, the learning platform can be considered as the mediating factor, which may be considered for further study in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies effectively improve peer-peer and student-facilitator interaction and engagement during virtual training, including embedding synchronous communications into videos such as polls during teaching audiences 28 or using other technologies to support active learning (e.g., padlet, use of chat, gamification). 29 Although effective, many technologies and pedagogies used to promote and sustain optimal interactions, particularly in the virtual space, require a significant amount of planning by facilitators.…”
Section: Discussionmentioning
confidence: 99%
“…Many educational institutions are using online learning technology in their learning process. It has proved to have a significant impact on education (Mayende et al, 2017). Online learning was used in recent years very effectively in teaching to enhance the traditional forms of teaching and learning (Isman & Dabaj, 2004).…”
Section: Online Learningmentioning
confidence: 99%